2011
DOI: 10.1111/j.1447-0594.2011.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Yearly diagnostic yield of colonoscopy in patients age 80 years or older, with a special interest in colorectal cancer

Abstract: The yield of colonoscopy in patients 80 years or older was high and constant over the years. The number of tumors rose less than expected compared to the increase of elderly in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
(27 reference statements)
2
14
0
Order By: Relevance
“…Generally, the yield of colonoscopy increases with age [4] . According to Surveillance Epidemiology End Results (SEER) registry data as of 2007, the incidence of CRC is 120 cases per 100000 in persons aged 50-64 years of age, 186 per 100000 in those 65-74, and 290.1 per 100000 in those ≥ 75 [5] .…”
Section: Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the yield of colonoscopy increases with age [4] . According to Surveillance Epidemiology End Results (SEER) registry data as of 2007, the incidence of CRC is 120 cases per 100000 in persons aged 50-64 years of age, 186 per 100000 in those 65-74, and 290.1 per 100000 in those ≥ 75 [5] .…”
Section: Yieldmentioning
confidence: 99%
“…Studies on symptomatic patients (including those with non-traversable obstructing lesions) report completion rates of around 83% [29] . Colonoscopy in the elderly is technically more challenging than in younger patients because of various factors, including more extensive diverticulosis, higher incidence of tortuosity or post-surgical adhesions, and higher risk of complications [4] . Elderly patients are also less likely to tolerate large amounts of sedation, and have a higher probability of suffering inadequate bowel preparation [13,30,31] , both of which can preclude complete colonoscopy.…”
Section: Colonoscopy Completion Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, others have reported a high yield of CRC and polyps. 23,31 However, these studies included a wide range of age groups and, in particular, did not distinguish between surveillance or screening examinations. Literature review on posttreatment CRC recurrence also found high rates of CRC recurrence but only followed up patients for the first 1 to 2 years after curative surgical resection.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, unexpectedly, the prevalence of colorectal neoplasia peaked in the eighth decade of life and declined thereafter ( P =0.009) 20. Loffeld et al21 also showed that the percentage of patients with CRC and polyps among the very elderly increases at a slow rate compared to the increase in the percentage of the very elderly in the general population. These findings may further limit the value of colonoscopy in the very elderly population, especially in screening indications for asymptomatic cases.…”
Section: Diagnostic Yield Of Colonoscopymentioning
confidence: 98%